DYNASTIC ETHOS AND CREATIVE WORK OF FAMILY (ex-libris of Kosachs’-Dragomanovs’). - Stasiuk, H. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the creative work of the literary dynasty in the light of the family ethos is analysed. On the basis of works of Kosachs’-Dragomanovs’ family of writers the influence of the authority of the ancestors on the moral-ethic determination of the literary heroes is followed. The conditional ex-libris of the gifted kin of Lesia Ukrainka – the motivation of moral «disposition» by chivalrous «code of honour» is described.